PERAN FOMO, YOLO DAN FINANCIAL ATTITUDE DALAM MEMBANGUN FINANCIAL PLANNING PADA GENERASI Z DI SUMBAWA - Anggita P. Aryani antika; Nova Adhitya Ananda (Publika Citra Media, 2026)
This study aims to determine the role of FOMO, YOLO and financial attitude in building financial planning in generation Z in Sumbawa. This study uses a quantitative method with a descriptive approach. The sample determination was obtained through non-probability sampling techniques and purposive sampling methods using the Hair formula so that 120 respondents were obtained. The data analysis technique used was the three box method with high, medium, and low index value categories. The results of this study are: (1) FOMO in Gen Z in Sumbawa appears in the form of a need to connect with social media, (2) YOLO in Gen Z in Sumbawa encourages the emergence of consumptive and impulsive behavior so that YOLO can reduce financial planning abilities, (3) Financial Attitude in Gen Z in Sumbawa can improve Gen Z's ability to build financial planning, and (4) Emotional bias in decision making in Gen Z in Sumbawa exacerbates the negative effects of FOMO and YOLO if they do not have good self-control.